Polarizing plate
Patent Information
- Application Number
- JP2024223987
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-03-11
AI Technical Summary
【0010】 本発明によれば、耐傷性に優れ、かつ、加熱耐久試験後に常温常湿環境下に長期間保管しても位相差フィルムにおけるクラックの発生が抑制された偏光板を提供することができる。
Smart Images

Figure 2025031811000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a polarizing plate, and further to a display device equipped with the polarizing plate. [Background technology]
[0002] Liquid crystal display devices (LCDs) are widely used not only in liquid crystal televisions, but also in mobile applications such as personal computers and mobile phones, and in-vehicle applications such as car navigation systems. Typically, liquid crystal display devices have a liquid crystal panel member in which polarizing plates are attached to both sides of a liquid crystal cell with an adhesive, and display is performed by controlling light from a backlight member with the liquid crystal panel member. In recent years, organic electroluminescence display devices have also begun to be widely used in mobile applications such as televisions and mobile phones, and in-vehicle applications such as car navigation systems, similar to liquid crystal display devices. In liquid crystal display devices and organic electroluminescence display devices, retardation films may be used to provide functions such as widening the viewing angle or preventing reflection of external light.
[0003] Polarizing plates are increasingly being installed in vehicles as optical elements that make up liquid crystal displays and organic electroluminescence displays. Polarizing plates used in vehicle-mounted displays are more often exposed to high-temperature environments than polarizing plates used in mobile applications such as televisions and mobile phones, and are therefore required to have smaller changes in properties at higher temperatures (high-temperature durability).
[0004] In-vehicle display devices, when used in car navigation systems, etc., require a touch panel function. In recent years, on-cell and in-cell display devices have been increasingly used as display devices with touch panel functions. In these types of display devices, a polarizing plate is placed on the outermost surface on the viewing side, so they are required to have high temperature durability as well as scratch prevention function (scratch resistance).
[0005] Patent Document 1 describes a polarizing plate including a retardation film made of a cyclic olefin resin film in order to expand the viewing angle. Patent Document 2 describes that a film using a cyclic olefin resin may be used as the retardation film that functions as a λ / 4 plate constituting the polarizing plate. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 5383594 [Patent Document 2] JP 2014-194483 A Summary of the Invention [Problem to be solved by the invention]
[0007] In the retardation film incorporated in a polarizing plate, such as the retardation film made of the above-mentioned cyclic olefin-based resin film, even if no cracks were found after the heat durability test, cracks were sometimes found when the film was subsequently stored for a long period of time under normal temperature and humidity conditions.
[0008] An object of the present invention is to provide a polarizing plate which has excellent scratch resistance and in which the occurrence of cracks in the retardation film is suppressed even when stored for a long period of time under a normal temperature and humidity environment after a heat durability test. [Means for solving the problem]
[0009] The present invention provides the following polarizing plate. [1] A polarizing film in which a dichroic dye is adsorbed and oriented on a polyvinyl alcohol-based resin film; a protective film having a hard coat layer provided on a substrate film; A retardation film having a tensile modulus of elasticity of 3000 MPa or less at a temperature of 23°C; Two or more of the protective films are laminated on the first surface side of the polarizing film, the retardation film is laminated on a second surface side of the polarizing film opposite to the first surface side. [2] At least one of the two or more protective films laminated on the first surface side has a moisture permeability of 200 g / m at a temperature of 40° C. and a relative humidity of 90%.2 The polarizing plate according to [1], wherein the polarizing plate has a wavelength of 100 nm or more. [3] Among the two or more protective films laminated on the first surface side, the protective film laminated closest to the polarizing film has a moisture permeability of 200 g / m at a temperature of 40° C. and a relative humidity of 90%. 2 The polarizing plate according to [1] or [2], wherein the polarizing plate has a wavelength of 100 nm or more. [4] The polarizing plate according to any one of [1] to [3], wherein the base film of at least one of the two or more protective films laminated on the first surface side is a cellulose-based resin film. [5] The polarizing plate according to any one of [1] to [4], wherein the retardation film is a cyclic olefin resin film. [6] The polarizing plate according to any one of [1] to [5], wherein the retardation film has an in-plane retardation value of 80 nm or more at a wavelength of 550 nm. [7] The polarizing plate according to any one of [1] to [6], further comprising a pressure-sensitive adhesive layer on the side of the retardation film opposite to the polarizing film side. [8] A display device having the polarizing plate according to [7] and a display element, The display device, wherein the polarizing plate is laminated on a display element via the pressure-sensitive adhesive layer. Effect of the Invention
[0010] According to the present invention, it is possible to provide a polarizing plate which has excellent scratch resistance and in which the occurrence of cracks in the retardation film is suppressed even when stored for a long period of time under a normal temperature and humidity environment after a heat durability test. [Brief description of the drawings]
[0011] [Figure 1] 1 is a schematic cross-sectional view showing a polarizing plate according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, preferred embodiments of the polarizing plate and the display device will be described with reference to the drawings. (Polarizing plate) Fig. 1 is a schematic cross-sectional view showing a polarizing plate according to this embodiment. The polarizing plate 1 includes a polarizing film 11 in which a dichroic dye is adsorbed and aligned on a polyvinyl alcohol-based resin film (hereinafter, sometimes referred to as a "PVA-based resin film"), protective films 12 and 13 in which a hard coat layer (hereinafter, sometimes referred to as an "HC layer") is provided on a base film, and a retardation film 21 in which a tensile modulus at a temperature of 23°C is 3000 MPa or less. As shown in Fig. 1, in the polarizing plate 1, two or more protective films 12 and 13 are laminated on a first surface 11a side of the polarizing film 11, and a retardation film 21 is laminated on a second surface 11b side of the polarizing film 11 opposite to the first surface 11a side.
[0013] As described above, in the polarizing plate 1, two or more protective films 12, 13 each including an HC layer are laminated on the first surface 11a side of the polarizing film 11. This can improve the pencil hardness of the surface of the polarizing plate 1 facing the protective films 12, 13, thereby imparting excellent scratch resistance to the polarizing plate 1.
[0014] The polarizing plate 1 can suppress the occurrence of cracks in the retardation film 21 even if it is kept in a room temperature and humidity environment of a temperature of 23°C and a relative humidity of 55% for about one month after a heat durability test in which it is kept at a temperature of 105°C for 500 hours. The reason for this is presumed to be as follows. If the polarizing plate 1 is cooled after the heat durability test and kept in a room temperature and humidity environment, moisture (water vapor) in the air is easily taken into the polarizing plate. The moisture taken into the polarizing plate causes a dimensional change in the polarizing film containing the PVA resin film. It is considered that if a force generated by the dimensional change of the polarizing film acts on the retardation film, cracks may occur in the retardation film. On the other hand, the polarizing plate 1 has two or more protective films 12, 13 laminated on the first surface 11a side of the polarizing film 11, the amount of moisture taken into the polarizing plate 1 can be suppressed, and further, the dimensional change of the polarizing film 11 can be suppressed. Therefore, it is presumed that the force acting on the retardation film 21 provided on the second surface 11b side of the polarizing film 11 can be reduced, and the occurrence of cracks in the retardation film 21 can be suppressed.
[0015] The films constituting the polarizing plate 1 can be laminated via bonding layers 31 to 33, as shown in Fig. 1. The bonding layers 31 to 33 are layers using an adhesive or a pressure-sensitive adhesive. The bonding layer 31 for bonding the protective film 12 and the protective film 13 is preferably a layer using a pressure-sensitive adhesive. The bonding layer 32 for bonding the protective film 13 and the polarizing film 11, and the bonding layer 33 for bonding the polarizing film 11 and the retardation film 21 are both preferably layers using an adhesive.
[0016] The polarizing plate 1 may further have functional layers such as an antistatic layer, a retardation layer other than the retardation film 21, and a protective layer other than the protective films 12 and 13 for protecting the surface of the polarizing film 11.
[0017] The polarizing plate 1 can be used as an optical element constituting a display device. Therefore, the polarizing plate 1 may have an adhesive layer 35 (FIG. 1) for bonding the polarizing plate 1 to a display element or the like of the display device. The polarizing plate 1 may further have a release film that covers and protects the adhesive layer 35 and is peelable from the adhesive layer 35.
[0018] (display device) The display device may include a polarizing plate 1 and a display element such as a liquid crystal cell or an organic electroluminescence (EL) element. In the display device, the polarizing plate 1 may be disposed so that the second surface 11b side of the polarizing film 11 faces the display element. The polarizing plate 1 may be laminated to the display element via an adhesive layer 35 shown in FIG. 1, and when the polarizing plate 1 does not have an adhesive layer 35, it may be laminated to the display element via an adhesive or bonding agent. Examples of the display device include a liquid crystal display device and an organic EL device.
[0019] The films and layers that constitute the polarizing plate 1 will be described in detail below. (Polarizing film) The polarizing film 11 is an absorptive polarizing film that has the property of absorbing linearly polarized light having a vibration plane parallel to its absorption axis and transmitting linearly polarized light having a vibration plane perpendicular to the absorption axis (parallel to the transmission axis). A suitable example of the polarizing film 11 is a uniaxially stretched PVA-based resin film having a dichroic dye adsorbed and oriented thereon.
[0020] The thickness of the polarizing film 11 is usually 50 μm or less, preferably 5 μm or more and 30 μm or less, more preferably 5 μm or more and 25 μm or less, and even more preferably 5 μm or more and 20 μm or less. By setting the thickness of the polarizing film 11 within these ranges, it is possible to maintain the handleability while preventing breakage, cracking, etc. during the production of the polarizing film 11, and to simultaneously achieve high optical properties. By setting the thickness of the polarizing film to 20 μm or less, it is possible to further suppress the decrease in visibility when placed in a high-temperature environment.
[0021] The polarizing film 11 can be produced by a method including, for example, a step of stretching a PVA-based resin film; a step of dyeing the PVA-based resin film with a dichroic dye to adsorb the dichroic dye; a step of treating the PVA-based resin film with the adsorbed dichroic dye with a crosslinking liquid such as an aqueous boric acid solution; and a step of washing with water after the step of treating with the crosslinking liquid.
[0022] The PVA-based resin film can be a film made of polyvinyl alcohol-based resin (hereinafter, sometimes referred to as "PVA-based resin"). Examples of PVA-based resins include saponified polyvinyl acetate-based resins. Examples of polyvinyl acetate-based resins include polyvinyl acetate, which is a homopolymer of vinyl acetate, as well as copolymers of vinyl acetate with other monomers copolymerizable therewith. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and (meth)acrylamides having an ammonium group. In this specification, "(meth)acrylic" means at least one selected from acrylic and methacrylic. The same applies to "(meth)acryloyl", "(meth)acrylate", etc.
[0023] The saponification degree of the PVA resin is usually 85 mol% or more and 100 mol% or less, and preferably 98 mol% or more. The PVA resin may be modified, and for example, polyvinyl formal or polyvinyl acetal modified with aldehydes can be used. The average polymerization degree of the PVA resin is usually 1000 or more and 10000 or less, and preferably 1500 or more and 5000 or less. The average polymerization degree of the PVA resin can be determined in accordance with JIS K 6726.
[0024] The method of forming a film from the PVA-based resin is not particularly limited, and a known method is adopted. The thickness of the PVA-based resin film used as the raw film when manufacturing the polarizing film is not particularly limited. For example, in order to make the thickness of the polarizing film 25 μm or less, the thickness of the PVA-based resin film as the raw film is preferably 40 μm or more and 75 μm or less, more preferably 45 μm or less.
[0025] The stretching of the PVA-based resin film is preferably uniaxial stretching. The uniaxial stretching can be performed before, simultaneously with, or after dyeing with a dichroic dye. When the uniaxial stretching is performed after dyeing, the uniaxial stretching may be performed before or during a crosslinking treatment. The uniaxial stretching may also be performed at these multiple stages. In the uniaxial stretching, the film may be uniaxially stretched between rolls having different peripheral speeds, or may be uniaxially stretched using a heated roll. The uniaxial stretching may be dry stretching in which the film is stretched in the air, or wet stretching in which the film is stretched in a state where the film is swollen with a solvent or water. The stretching ratio is usually 3 to 8 times.
[0026] As a method for dyeing a PVA-based resin film with a dichroic dye, for example, a method of immersing the PVA-based resin film in an aqueous solution containing the dichroic dye is adopted. As the dichroic dye, iodine or a dichroic organic dye is used. It is preferable to immerse the PVA-based resin film in water before the dyeing process.
[0027] As a crosslinking treatment after dyeing with a dichroic dye, a method of immersing the dyed PVA resin film in an aqueous solution containing boric acid is usually adopted. When iodine is used as the dichroic dye, the aqueous solution containing boric acid preferably contains potassium iodide.
[0028] (Protective film) The protective films 12 and 13 each have a base film and an HC layer. The protective films 12 and 13 preferably have the HC layer formed so as to be in direct contact with the base film. The HC layer is preferably provided on one side of the base film, but may be provided on both sides.
[0029] The number of protective films 12, 13 laminated on the first surface 11a side of the polarizing film 11 (hereinafter, two or more protective films laminated on the first surface 11a side may be collectively referred to as the "protective film group") is preferably 5 or less, more preferably 3 or less, and most preferably 2. If the protective film group includes six or more protective films, it becomes difficult to adjust the curl (warping) of the polarizing plate 1. As shown in FIG. 1, the protective films 12, 13 constituting the protective film group are preferably laminated via an attachment layer 31, and both sides of the attachment layer 31 are more preferably in direct contact with the protective films 12, 13 constituting the protective film group. In both of the protective films 12, 13 constituting the protective film group, it is preferable that the base film is disposed on the polarizing film 11 side of the polarizing plate 1, and the HC layer is disposed on the front side of the polarizing plate 1 (opposite the polarizing film 11 side).
[0030] The thickness of the protective film is not particularly limited, but is usually 1 μm or more and 100 μm or less, and from the viewpoint of strength and handleability, it is preferably 5 μm or more and 60 μm or less, more preferably 10 μm or more and 55 μm or less, and even more preferably 15 μm or more and 50 μm or less.
[0031] The protective films 12 and 13 constituting the protective film group may have the same or both of the materials and thicknesses of the base film and the HC layer, or may have different materials and thicknesses of the base film and the HC layer.
[0032] At least one of the protective films has a moisture permeability of 200 g / m at a temperature of 40° C. and a relative humidity of 90%. 2 ·day or more is preferable, and 300g / m 2·day or more is more preferable, and the upper limit is usually 5000g / m 2 -day or less, 2000g / m 2 ·day or less is preferable, and 1000g / m 2 ·days or less. In polarizing plate 1, it is sufficient that at least one of the protective films in the protective film group has a moisture permeability in the above range. By setting the moisture permeability of the protective film in the above range, it is possible to prevent polarizing film 11 from becoming polyenic and becoming colored in the heat durability test described later.
[0033] It is preferable that the protective film 12 laminated closest to the polarizing film side among the protective films has a moisture permeability in the above range. When manufacturing the polarizing plate 1, as described below, the protective film 12 may be laminated to the polarizing film 11 using an adhesive (adhesive or pressure sensitive adhesive) such as a water-based adhesive, and then the laminating layer 32 may be formed by a drying process, and then the protective film 13 may be laminated. In this case, by setting the moisture permeability of the protective film 12 laminated closest to the polarizing film 11 among the protective films to the above range, moisture contained in the adhesive can be easily removed by the drying process.
[0034] As long as the protective film 12 laminated closest to the polarizing film 11 side of the protective film group has a moisture permeability within the above range, the moisture permeability of the other protective films 13 other than the protective film 12 included in the protective film group is not particularly limited. The moisture permeability of the other protective films 13 may be lower than that of the protective film 12. The moisture permeability of the other protective films 13 at a temperature of 40° C. and a relative humidity of 90% is not particularly limited, but is preferably 1000 g / m 2 ·day or less, and 500g / m 2 It is more preferable that the moisture permeability of the protective film 13 is 20 g / m 2 or less. 2 ・day or more is preferable, and 30g / m 2·days or more is more preferable. By setting the upper limit of the moisture permeability of the other protective film 13 within the above range, the rate of moisture uptake into the polarizing plate 1 after the heat durability test can be suppressed. As a result, it is thought that the time for stress relaxation of the polarizing film 11 can be easily secured, and therefore the occurrence of cracks in the retardation film 21 can be suppressed. By setting the lower limit of the moisture permeability of the other protective film 13 within the above range, it is possible to suppress the polarizing film 11 from becoming polyenic and becoming discolored during the heat durability test. The moisture permeability of the protective films 12 and 13 can be measured by the method described in the examples described later.
[0035] In the above, the moisture permeability of the protective film 12 is 200 g / m 2 ·day or more, and the moisture permeability of the other protective film 13 is 1000g / m 2 ·days or less has been described, but even if this moisture permeability relationship is reversed, it is possible to prevent the polarizing film 11 from becoming polyenic and becoming colored in the heat durability test.
[0036] The base film constituting the protective films 12 and 13 is not particularly limited, but is preferably made of a resin material having excellent transparency, mechanical strength, thermal stability, moisture shielding properties, etc. Examples of such resin materials include one or more of methyl (meth)acrylate resins, polyolefin resins, cyclic olefin resins, polyvinyl chloride resins, cellulose resins, styrene resins, acrylonitrile-butadiene-styrene resins, acrylonitrile-styrene resins, polyvinyl acetate resins, polyvinylidene chloride resins, polyamide resins, polyacetal resins, polycarbonate resins, modified polyphenylene ether resins, polybutylene terephthalate resins, polyethylene terephthalate resins, polysulfone resins, polyethersulfone resins, polyarylate resins, polyamideimide resins, and polyimide resins. These resins may be used after any suitable polymer modification. Examples of polymer modification include copolymerization, crosslinking, molecular end modification, stereoregularity control, and mixing including reactions between different polymers.
[0037] The base film of at least one of the protective films in the protective film group is preferably a cellulose-based resin film formed using a cellulose-based resin as the resin material. It is more preferable that the base films of all of the protective films constituting the protective film group are cellulose-based resin films.
[0038] The cellulose-based resin may be an organic acid ester or mixed organic acid ester of cellulose in which some or all of the hydrogen atoms in the hydroxyl groups of cellulose are replaced with acetyl groups, propionyl groups, and / or butyryl groups. For example, cellulose acetate, propionate, butyrate, and mixed esters thereof may be used. Among them, triacetyl cellulose, diacetyl cellulose, cellulose acetate propionate, cellulose acetate butyrate, and the like are preferred.
[0039] The resin material constituting the substrate film may contain appropriate additives within the range that does not impair transparency. Examples of additives include antioxidants, ultraviolet absorbers, antistatic agents, lubricants, nucleating agents, antifogging agents, antiblocking agents, retardation reducing agents, stabilizers, processing aids, plasticizers, impact resistance aids, matting agents, antibacterial agents, and fungicides. These additives may be used alone or in combination.
[0040] The thickness of the base film is not particularly limited, but may be, for example, 1 μm or more, may be 3 μm or more, may be 10 μm or more, may be 30 μm or more, and is usually 90 μm or less, may be 70 μm or less, may be 60 μm or less, or may be 50 μm or less. The base film usually has a single-layer structure, but may have a multi-layer structure of two or more layers.
[0041] The HC layer constituting the protective film 12, 13 is not particularly limited, but is preferably a cured layer of an ultraviolet-curable resin formed on a substrate film. Examples of ultraviolet-curable resins include (meth)acrylic resins, silicone resins, polyester resins, urethane resins, amide resins, and epoxy resins. The HC layer may contain additives to improve the surface hardness. Examples of additives include, but are not particularly limited to, inorganic fine particles, organic fine particles, or mixtures thereof.
[0042] The thickness of the HC layer is preferably 10 μm or less, more preferably 8 μm or less, and is usually 0.1 μm or more, may be 1 μm or more, or may be 4 μm or more. If the thickness of the HC layer exceeds 10 μm, the curl (warping) of the protective films 12 and 13 becomes large, making it difficult to adjust the curl of the polarizing plate 1.
[0043] The protective films 12 and 13 preferably have a hardness of H or more, more preferably 2H or more, may be 3H or more, or may be 4H or more, when measured by a pencil hardness test specified in JIS K 5600-5-4:1999 "General test methods for paints - Part 5: Mechanical properties of coatings - Section 4: Scratch hardness (pencil method)" (when a substrate film with an HC layer formed thereon is placed on a glass plate and measurement is performed on the HC layer side).
[0044] The HC layer can be formed, for example, by applying a composition for forming an HC layer (hereinafter sometimes referred to as "composition for forming an HC layer") containing an ultraviolet-curable resin and, if necessary, additives, etc., onto a base film, and curing the composition by exposure to ultraviolet light.
[0045] (Retardation film) The retardation film 21 is a film having a retardation, and is usually a stretched film obtained by stretching a resin film. The retardation film 21 preferably has a single-layer structure. The tensile modulus of the retardation film 21 at a temperature of 23° C. is 3000 MPa or less, and may be 2800 MPa or less, and is usually 1000 MPa or more, and may be 2000 MPa or more. The tensile modulus can be measured by the method described in the examples below.
[0046] An example of the retardation film 21 having the above tensile modulus is an olefin-based resin film formed using an olefin-based resin. Examples of the olefin-based resin include resins that mainly contain structural units derived from chain aliphatic olefins such as ethylene and propylene, or alicyclic olefins such as norbornene and its substitutes (hereinafter, these may be collectively referred to as "norbornene-based monomers"). "Mainly containing structural units" means that the proportion of structural units contained in the resin is 50% or more on a substance weight basis. The olefin-based resin may be a copolymer using two or more types of monomers.
[0047] The retardation film 21 is preferably a cyclic olefin resin film formed using a cyclic olefin resin, which is a resin mainly containing structural units derived from an alicyclic olefin. A typical example of an alicyclic olefin constituting a cyclic olefin resin is a norbornene monomer. Norbornene is a compound in which one carbon-carbon bond of norbornane becomes a double bond, and is named bicyclo[2,2,1]hept-2-ene according to the IUPAC nomenclature. Examples of norbornene substitutions include 3-substitutions, 4-substitutions, and 4,5-disubstitutions, with the double bond positions of norbornene being 1,2-positions, and further include dicyclopentadiene and dimethanooctahydronaphthalene.
[0048] The cyclic olefin resin may or may not have a norbornane ring in its constituent unit. The norbornene monomer forming the cyclic olefin resin without a norbornane ring in its constituent unit is, for example, a monomer that becomes a 5-membered ring by ring opening, typically, norbornene, dicyclopentadiene, 1- or 4-methylnorbornene, and 4-phenylnorbornene. When the cyclic olefin resin is a copolymer, the molecular arrangement is not particularly limited, and may be a random copolymer, a block copolymer, or a graft copolymer.
[0049] More specific examples of the cyclic olefin resin include, for example, a ring-opening polymer of a norbornene monomer, a ring-opening copolymer of a norbornene monomer and another monomer, a polymer modified product obtained by adding maleic acid or cyclopentadiene to the above-mentioned polymers, and a polymer or copolymer obtained by hydrogenating the above-mentioned polymers; an addition polymer of a norbornene monomer, and an addition copolymer of a norbornene monomer and another monomer. Examples of other monomers in the case of copolymerization include α-olefins, cycloalkenes, and non-conjugated dienes. The cyclic olefin resin may also be a copolymer using one or more of a norbornene monomer and another alicyclic olefin. Among these, the cyclic olefin resin is preferably a resin obtained by hydrogenating a ring-opening polymer or ring-opening copolymer using a norbornene monomer.
[0050] Commercially available cyclic olefin resins using the norbornene monomers include "ZEONEX" and "ZEONOR" sold by Zeon Corporation, and "ARTON" sold by JSR Corporation. Films of these cyclic olefin resins and stretched films thereof are also commercially available, and examples of such products include "ZEONOR Film" sold by Optes Corporation, "ARTON Film" sold by JSR Corporation, and "ESCINA" sold by Sekisui Chemical Co., Ltd.
[0051] The retardation film 21 may be a film made of a mixed resin containing two or more kinds of olefin resins, or a film made of a mixed resin of an olefin resin and another thermoplastic resin. For example, a mixed resin containing two or more kinds of olefin resins may be a mixture of a cyclic olefin resin and a chain aliphatic olefin resin as described above. When a mixed resin of an olefin resin and another thermoplastic resin is used, the other thermoplastic resin is appropriately selected depending on the purpose. Specific examples of other thermoplastic resins include polyvinyl chloride resins, cellulose resins, polystyrene resins, acrylonitrile / butadiene / styrene copolymer resins, acrylonitrile / styrene copolymer resins, (meth)acrylic resins, polyvinyl acetate resins, polyvinylidene chloride resins, polyamide resins, polyacetal resins, polycarbonate resins, modified polyphenylene ether resins, polybutylene terephthalate resins, polyethylene terephthalate resins, polyphenylene sulfide resins, polysulfone resins, polyethersulfone resins, polyetheretherketone resins, polyarylate resins, liquid crystal resins, polyamideimide resins, polyimide resins, and polytetrafluoroethylene resins. These thermoplastic resins can be used alone or in combination of two or more. The thermoplastic resins can also be used after any suitable polymer modification. Examples of polymer modification include copolymerization, crosslinking, molecular end modification, and stereoregularity impartation.
[0052] When a mixed resin of an olefin resin and another thermoplastic resin is used, the content of the other thermoplastic resin is usually about 50% by weight or less, preferably about 40% by weight or less, based on the total resin. By setting the content of the other thermoplastic resin within this range, a retardation film 21 can be obtained that has a small absolute value of the photoelastic coefficient, exhibits good wavelength dispersion characteristics, and is excellent in durability, mechanical strength, and transparency.
[0053] The retardation film 21 may contain other components as necessary, such as a residual solvent, a stabilizer, a plasticizer, an antiaging agent, an antistatic agent, and an ultraviolet absorbing agent, etc. In addition, the retardation film 21 may contain a leveling agent to reduce surface roughness.
[0054] The retardation film 21 preferably has an in-plane retardation value, and the in-plane retardation value at a wavelength of 550 nm is preferably 80 nm or more, may be 90 nm or more, may be 100 nm or more, and may be 300 nm or less, or may be 200 nm or less. The retardation film 21 is preferably a stretched film.
[0055] In general, the higher the in-plane retardation value of the retardation film 21, the more uniform the molecular orientation of the retardation film 21 is, so that the retardation film 21 is more likely to crack when subjected to external force. As described above, the polarizing plate 1 has a structure in which two or more protective films 12, 13 are laminated on the first surface 11a of the polarizing film 11. Therefore, even if the polarizing plate 1 including the retardation film 21 having the above-mentioned high in-plane retardation value is kept for a long period of time under a normal temperature and humidity environment after a heat durability test, the dimensional change of the polarizing film 11 can be suppressed, and the force acting on the retardation film 21 can be reduced accordingly, so that the occurrence of cracks in the retardation film 21 can be suppressed.
[0056] The in-plane retardation value of the retardation film 21 can be measured by the method described in the Examples below. The in-plane retardation value Re(λ) of the retardation film 21 at a wavelength λ [nm] refers to the in-plane retardation value of the retardation film 21 at a temperature of 23° C., and is calculated by the following formula (i). Re(λ)=(nx-ny)×d(i) [In formula (i), nx is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), ny is the refractive index in the in-plane direction perpendicular to the slow axis, d is the thickness [nm] of the retardation film 21.
[0057] The retardation film 21 may have a thickness direction retardation value of 0 (zero) or may have a thickness direction retardation value. The thickness direction retardation value of the retardation film 21 at a wavelength of 550 nm may be, for example, 10 nm or more, 20 nm or more, 40 nm or more, 100 nm or less, 80 nm or less, or 60 nm or less. The thickness direction retardation value of the retardation film 21 can be measured by a method described in the examples below. The thickness direction retardation value Rth(λ) of the retardation film 21 at a wavelength λ [nm] refers to the thickness direction retardation value of the retardation film 21 at a temperature of 23° C., and is calculated by the following formula (ii). Rth(λ)=〔{(nx+ny) / 2}-nz〕×d (ii) [In formula (ii), nx is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), ny is the refractive index in the in-plane direction perpendicular to the slow axis, nz is the refractive index in the thickness direction, d is the thickness [nm] of the retardation film 21.
[0058] The thickness of the retardation film 21 is not particularly limited, but is preferably 15 μm to 80 μm, more preferably 18 μm to 45 μm, and most preferably 20 μm to 30 μm. If the thickness of the retardation film is less than 15 μm, the film is difficult to handle and tends to be difficult to achieve a predetermined retardation value. On the other hand, if the thickness of the retardation film is more than 80 μm, the film tends to be poor in processability, low in transparency, and heavy in weight of the obtained polarizing plate 1.
[0059] The retardation film 21 can be obtained by stretching a resin film formed using the above-mentioned resin. The resin film can be obtained, for example, by forming a film by a casting method or a melt extrusion method from a solution containing the above-mentioned olefin resin. When forming a film using a mixed resin of two or more kinds, the film formation method is not particularly limited, and examples thereof include a method of forming a film by a casting method using a homogeneous solution obtained by stirring and mixing resin components with a solvent at a predetermined ratio, and a method of melt-mixing resin components at a predetermined ratio and forming a film by a melt extrusion method.
[0060] Examples of the stretching treatment of the resin film include known longitudinal uniaxial stretching, tenter transverse uniaxial stretching, simultaneous biaxial stretching, sequential biaxial stretching, etc. In the stretching treatment, in addition to appropriately adjusting the stretching ratio and stretching speed so as to obtain a desired retardation value, various temperatures such as a preheating temperature, a stretching temperature, a heat setting temperature, a cooling temperature, etc. during stretching, and their patterns may be appropriately selected.
[0061] When the retardation film 21 is the above-mentioned cyclic olefin resin film, for example, the retardation film 21 can be obtained by forming a film-like material using the above-mentioned cyclic olefin resin and subjecting it to a stretching treatment in advance, laminating a shrinkable film having a predetermined shrinkage rate thereto, and then heat shrinking the film. This makes it possible to obtain a retardation film 21 having high uniformity and a large retardation value.
[0062] (Functional layer) The polarizing plate 1 may have one or more functional layers, such as an antistatic layer, a retardation layer other than the retardation film 21, or a protective layer other than the protective films 12 and 13 for covering and protecting the surface of the polarizing film 11.
[0063] The antistatic layer is a layer for suppressing the polarizing plate 1 from being charged. The antistatic layer usually contains an antistatic agent such as an ionic compound, and can be, for example, a layer containing an antistatic agent and a resin. For example, the antistatic layer can be provided in the polarizing plate 1 between the polarizing film 11 and the retardation film 21, between the polarizing film 11 and the protective film 12, on the opposite side of the retardation film 21 to the polarizing film 11, or the like. The antistatic layer is preferably laminated to these films via an attachment layer.
[0064] The other retardation layer is a layer having an in-plane retardation value or a retardation value in the thickness direction. The other retardation layer can be, for example, a retardation layer having a retardation value in the thickness direction at a wavelength of 550 nm, and can be, for example, a positive C plate. The positive C plate is used, for example, when the polarizing plate 1 is used in an IPS mode liquid crystal display device or the like. The other retardation layer can be provided, for example, between the polarizing film 11 and the retardation film 21, or on the opposite side of the retardation film 21 to the polarizing film 11 side. The other retardation layer may be a stretched film obtained by stretching a resin film, or may be a cured layer of a polymerizable liquid crystal compound. The other retardation layer can be laminated to the polarizing film 11 and the retardation film 21 via an attachment layer. When the other retardation layer is a cured layer, it can also be provided so as to be in direct contact with these films by polymerizing and curing a polymerizable liquid crystal compound applied to the polarizing film 11 or the retardation film 21.
[0065] The other protective layer is a layer for covering and protecting the first surface 11a or the second surface 11b of the polarizing film 11. The other protective layer is preferably provided on the second surface 11b side of the polarizing film 11, and is preferably provided between the polarizing film 11 and the retardation film 21 via an attachment layer. In this case, the attachment layer provided between the polarizing film 11 and the other protective layer is preferably provided so as to be in contact with the polarizing film 11 and the other protective layer, respectively, and the attachment layer provided between the other protective layer and the retardation film 21 is preferably provided so as to be in contact with the other protective layer and the retardation film 21, respectively. The other protective layer may be a film formed using the resin material described in the base film constituting the protective films 12 and 13. The other protective layer preferably does not have a retardation, and may be, for example, a cellulose-based resin film having no retardation, or a cyclic olefin-based resin film having no retardation.
[0066] (Lamination layer) Examples of the bonding layers 31 to 33 for bonding the films and layers constituting the polarizing plate 1 include layers formed using a known adhesive or layers formed using a known pressure-sensitive adhesive.
[0067] The adhesive is an adhesive other than a pressure-sensitive adhesive (adhesive), and examples thereof include a water-based adhesive, an active energy ray curable adhesive, and a thermosetting adhesive, and preferably a water-based adhesive and an active energy ray curable adhesive. The thickness of the attachment layer formed using the adhesive may be, for example, 0.01 μm or more, 0.1 μm or more, 0.5 μm or more, or 1 μm or more, and may be, for example, 20 μm or less, 15 μm or less, 10 μm or less, or 5 μm or less.
[0068] Examples of the aqueous adhesive include an adhesive made of an aqueous polyvinyl alcohol resin solution, an aqueous two-liquid urethane emulsion adhesive, and the like. Among them, an aqueous adhesive made of an aqueous polyvinyl alcohol resin solution is preferably used. Examples of the polyvinyl alcohol resin include a vinyl alcohol homopolymer obtained by saponifying polyvinyl acetate, which is a homopolymer of vinyl acetate, a polyvinyl alcohol copolymer obtained by saponifying a copolymer of vinyl acetate and another monomer copolymerizable therewith, and a modified polyvinyl alcohol polymer in which the hydroxyl groups of these are partially modified. The aqueous adhesive may contain a crosslinking agent such as an aldehyde compound (such as glyoxal), an epoxy compound, a melamine compound, a methylol compound, an isocyanate compound, an amine compound, or a polyvalent metal salt.
[0069] When a water-based adhesive is used as the adhesive, it is preferable to carry out a drying step to remove water contained in the water-based adhesive after lamination with the film to be laminated. After the drying step, a curing step may be carried out, for example, at a temperature of 20 to 45°C.
[0070] The active energy ray curable adhesive is an adhesive containing a curable compound that is cured by irradiation with active energy rays such as ultraviolet rays, visible light, electron beams, and X-rays, and is preferably an ultraviolet ray curable adhesive. The curable compound can be a cationic polymerizable curable compound or a radical polymerizable curable compound. Examples of the cationic polymerizable curable compound include an epoxy-based compound (a compound having one or more epoxy groups in the molecule), an oxetane-based compound (a compound having one or more oxetane rings in the molecule), or a combination thereof. Examples of the radical polymerizable curable compound include a (meth)acrylic-based compound (a compound having one or more (meth)acryloyloxy groups in the molecule), other vinyl-based compounds having a radical polymerizable double bond, or a combination thereof. A cationic polymerizable curable compound and a radical polymerizable curable compound may be used in combination. The active energy ray curable adhesive usually further contains a cationic polymerization initiator and / or a radical polymerization initiator for initiating the curing reaction of the curable compound.
[0071] The adhesive exerts adhesive properties by attaching itself to an adherend, and is so-called a pressure-sensitive adhesive. The adhesive can be composed of an adhesive composition mainly composed of a resin such as a (meth)acrylic, rubber, urethane, ester, silicone, or polyvinyl ether resin. Among them, an adhesive composition having a (meth)acrylic resin as a base polymer, which is excellent in transparency, weather resistance, heat resistance, etc., is preferable. The adhesive may be an active energy ray curable type or a heat curable type. The thickness of the attachment layer formed using the adhesive is usually 3 μm or more and 30 μm or less, and preferably 3 μm or more and 25 μm or less.
[0072] As the (meth)acrylic resin (base polymer) contained in the pressure-sensitive adhesive composition, for example, a polymer or copolymer containing one or more (meth)acrylic acid esters as a monomer, such as butyl (meth)acrylate, ethyl (meth)acrylate, isooctyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate, is preferably used. It is preferable to copolymerize a polar monomer into the base polymer. Examples of the polar monomer include monomers having a carboxyl group, a hydroxyl group, an amide group, an amino group, an epoxy group, and the like, such as (meth)acrylic acid, 2-hydroxypropyl (meth)acrylate, hydroxyethyl (meth)acrylate, (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, and glycidyl (meth)acrylate.
[0073] The adhesive composition may contain only the base polymer, but usually further contains a crosslinking agent. Examples of the crosslinking agent include divalent or higher metal ions that form a carboxylate metal salt with a carboxyl group; polyamine compounds that form an amide bond with a carboxyl group; polyepoxy compounds or polyols that form an ester bond with a carboxyl group; and polyisocyanate compounds that form an amide bond with a carboxyl group. Among them, polyisocyanate compounds are preferred.
[0074] (Adhesive layer) The polarizing plate 1 may have an adhesive layer 35 for attaching the polarizing plate 1 to a display element of a display device or the like. The adhesive layer 35 is preferably provided on the side of the retardation film 21 of the polarizing plate 1 opposite to the polarizing film 11 side. The adhesive layer 35 can be formed using an adhesive. Examples of the adhesive include the adhesives used to form the above-mentioned attachment layer. The thickness of the adhesive layer 35 is not particularly limited, but is usually 3 μm or more and 50 μm or less, preferably 5 μm or more and 40 μm or less, and may be 10 μm or more and 30 μm or less.
[0075] (Release film) The polarizing plate 1 may have a release film that is peelable from the adhesive layer 35. The release film is used to cover and protect the surface of the adhesive layer 35 or to support the adhesive layer 35. An example of the release film is a film in which a surface of the base resin film on the side of the adhesive layer 35 has been subjected to a release treatment such as silicone treatment. An example of the resin material constituting the base resin film is a film formed using the resin material described above for the base film. The base resin film may have a single layer structure or a multilayer structure of two or more layers.
[0076] (Method of manufacturing polarizing plate) The method for producing the polarizing plate 1 is not particularly limited, and a known method can be used. For example, the protective film 12 is laminated on the first surface 11a of the polarizing film 11 using a water-based adhesive, the retardation film 21 is laminated on the second surface 11b of the polarizing film 11 using a water-based adhesive, and a drying process is performed to remove water from the water-based adhesive to produce a laminate of the protective film 12 / attaching layer 32 / polarizing film 11 / attaching layer 33 / retardation film 21. In this case, if the thickness difference between the protective film 12 and the retardation film 21 is 30 μm or less, curling that occurs in the laminate is easily suppressed, and a flat laminate is easily obtained. Thereafter, the protective film 13 is laminated on the protective film 12 side of the laminate via the attaching layer 31, thereby obtaining the polarizing plate 1. When the polarizing plate 1 has three or more protective films on the first surface 11a side of the polarizing film 11, a process of laminating a protective film may be further performed. When a laminate in which the difference in thickness between the protective film 12 and the retardation film 21 is 30 μm or less is used as described above, curling of the polarizing plate 1 is easily suppressed, and a flat polarizing plate 1 is easily obtained.
[0077] In order to enhance the adhesion between the films and layers (protective films 12, 13, polarizing film 11, retardation film 21, functional layer, etc.) constituting the polarizing plate 1 and the laminating layer, the laminating surfaces of these films and layers may be subjected to a surface activation treatment. Examples of the surface activation treatment include dry treatments such as corona treatment, plasma treatment, discharge treatment (glow discharge treatment, etc.), flame treatment, ozone treatment, UV ozone treatment, and ionizing active ray treatment (ultraviolet ray treatment, electron beam treatment, etc.); and wet treatments such as ultrasonic treatment using a solvent such as water or acetone, saponification treatment, and anchor coat treatment. These surface activation treatments may be performed alone or in combination of two or more. EXAMPLES
[0078] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0079] [Thickness measurement] The thickness of each film and layer constituting the polarizing plate was measured using a digital micrometer MH-15M manufactured by Nikon Corporation.
[0080] [Measurement of moisture permeability] The moisture permeability of the protective film was measured in accordance with JIS K 7129:2008 Appendix B in an atmosphere at a temperature of 40°C and a relative humidity of 90%.
[0081] [Measurement of phase difference value] The retardation values of the retardation film and other retardation layers were measured using a retardation measuring device KOBRA-WPR (manufactured by Oji Scientific Instruments Co., Ltd.).
[0082] [Measurement of tensile modulus] A test piece having a width of 15 mm and a length of 150 mm was cut out from the retardation film parallel to the slow axis and the fast axis. Next, the test piece was clamped at both ends in the long side direction with the upper and lower grips of a tensile tester (AUTOGRAPH (registered trademark) AG-1S tester manufactured by Shimadzu Corporation) so that the distance between the grips was 100 mm, and pulled at a pulling speed of 50 mm / min in an environment of 23 ° C. to create a stress-strain curve, and the tensile modulus in the direction parallel to the slow axis and the fast axis at 23 ° C. was calculated. The larger value of the tensile modulus in the direction parallel to the slow axis and the fast axis calculated in this way was taken as the tensile modulus of the retardation film at 23 ° C.
[0083] [Measurement of storage modulus] The storage modulus G' of the pressure-sensitive adhesive layer A and the pressure-sensitive adhesive layer B was measured according to the following procedures [I] to [III]. [I] Two samples, each weighing 25±1 mg, are taken from each adhesive layer, and each sample is molded into an approximately ball-like shape. [II] The two molded roughly ball-shaped samples are attached to the top and bottom surfaces of an I-shaped jig, and both the top and bottom surfaces are sandwiched between L-shaped jigs to prepare a measurement sample. The measurement sample has a configuration of L-shaped jig / adhesive layer A or adhesive layer B / I-shaped jig / adhesive layer / L-shaped jig. [III] The storage modulus G' of the measurement sample is measured using a dynamic viscoelasticity measuring device "DVA-220" manufactured by IT Measurement and Control Co., Ltd. under the conditions of a temperature of 23°C, a frequency of 1 Hz, and an initial strain of 1 N.
[0084] [Measurement of pencil hardness] The protective film was placed on a glass plate so that the base film side of the protective film faced the glass plate. The pencil hardness test specified in JIS K 5600-5-4:1999 "General test methods for paints - Part 5: Mechanical properties of coatings - Section 4: Scratch hardness (pencil method)" was carried out on the HC layer side of the protective film to measure the pencil hardness of the protective film.
[0085] <Preparation of polarizing film> A 40 μm thick PVA resin film made of a PVA resin with an average degree of polymerization of about 2400 and a degree of saponification of 99.9 mol% or more was prepared. This PVA resin film was uniaxially stretched by about 5 times in a dry state, and further immersed in pure water at a temperature of 60° C. for 1 minute while maintaining the tension. Then, the PVA resin film was immersed in an aqueous solution with a weight ratio of iodine / potassium iodide / water of 0.05 / 5 / 100 at a temperature of 28° C. for 60 seconds. Then, the PVA resin film was immersed in an aqueous solution with a weight ratio of potassium iodide / boric acid / water of 8.5 / 8.5 / 100 at a temperature of 72° C. for 300 seconds. Then, the film was washed with pure water at a temperature of 26° C. for 20 seconds, and then dried at a temperature of 65° C. In this way, a polarizing film with a thickness of 15 μm was obtained in which iodine as a dichroic dye was adsorbed and aligned on the PVA resin film.
[0086] <Preparation of protective film (1)> The components shown below were mixed to prepare a composition for forming an HC layer. PET30 97.0 parts by mass Irgacure 907 3.0 parts by weight MEK 81.8 parts by mass Here, PET30 is a mixture of pentaerythritol tetraacrylate and pentaerythritol triacrylate (manufactured by Nippon Kayaku Co., Ltd.). Irgacure 907 is a photopolymerization initiator (manufactured by BASF). MEK is methyl ethyl ketone.
[0087] A rolled substrate film (cellulose acylate film TD40, manufactured by Fujifilm Corporation, width 1,340 mm, film thickness 40 μm) was unwound, and the composition for forming an HC layer was applied thereto by a die coating method using a slot die at a conveying speed of 30 m / min, and the coating layer was dried at 60° C. for 150 seconds to form a coating layer. Thereafter, under conditions of nitrogen purging and an oxygen concentration of about 0.1%, an air-cooled metal halide lamp (manufactured by Eye Graphics Co., Ltd.) with an output of 160 W / cm was used to apply an illuminance of 400 mW / cm. 2 , irradiation amount 120mJ / cm 2The coating layer was cured by irradiating ultraviolet rays of 250 g / m2 to form an HC layer. The coating thickness of the coating layer was adjusted so that the film thickness of the HC layer was 7 μm. In this way, a protective film (1) having an HC layer on one side of the base film was obtained and rolled up. The moisture permeability of the protective film (1) was 250 g / m2. 2 The pencil hardness of the protective film (1) was 2H.
[0088] <Preparation of protective film (2)> A protective film (2) was obtained in the same manner as in the preparation of the protective film (1), except that the thickness of the coating layer was adjusted so that the thickness of the HC layer was 5 μm. The moisture permeability of the protective film (2) was 350 g / m 2 The pencil hardness of the protective film (2) was 3H.
[0089] <Preparation of protective film (3)> A protective film (3) was obtained in the same manner as in the preparation of the protective film (1), except that the thickness of the coating layer was adjusted so that the thickness of the HC layer was 3 μm. The moisture permeability of the protective film (3) was 500 g / m 2 The pencil hardness of the protective film (3) was 3H.
[0090] <Preparation of Retardation Laminate Including Retardation Film and Other Retardation Layer> A retardation film and other retardation layers were produced according to the description in paragraphs
[0106] to
[0109] of International Publication No. 2018 / 207798. Specifically, an unstretched cycloolefin polymer film (manufactured by JSR Corporation, product name "Arton Film") was uniaxially stretched to obtain a retardation film having a thickness of 24 μm. The tensile modulus of the obtained retardation film at a temperature of 23° C. was measured to be 2742 MPa. In addition, the in-plane retardation value Re(550) of the retardation film at a wavelength of 550 nm was 110 nm, and the retardation value Rth(550) in the thickness direction at a wavelength of 550 nm was 55 nm.
[0091] Next, a composition having a rod-shaped liquid crystal compound was applied to one side of the retardation film obtained above to form another retardation layer, thereby obtaining a retardation laminate. The in-plane retardation value Re(550) of the other retardation layer at a wavelength of 550 nm was 0 nm, and the retardation value Rth(550) in the thickness direction at a wavelength of 550 nm was -100 nm.
[0092] <Preparation of polyvinyl alcohol adhesive (PVA adhesive)> 50 g of modified PVA resin containing acetoacetyl groups (Mitsubishi Chemical Corporation: Gohsenex Z-410) was dissolved in 950 g of pure water, heated at 90°C for 2 hours, and then cooled to room temperature to obtain a polyvinyl alcohol solution. Next, the polyvinyl alcohol solution, maleic acid, glyoxal, and pure water were mixed so that each compound had the following concentration to prepare a PVA adhesive. Polyvinyl alcohol concentration: 3.0% by weight Maleic acid concentration: 0.01% by weight Glyoxal concentration: 0.15% by weight
[0093] <Preparation of Adhesive Layer A and Adhesive Layer B> As adhesive layer A, a commercially available sheet-shaped acrylic adhesive (storage modulus at a temperature of 23° C.: 0.06 MPa) having a thickness of 5 μm was prepared. As adhesive layer B, a commercially available sheet-shaped acrylic adhesive (storage modulus at a temperature of 23° C.: 0.06 MPa) having a thickness of 25 μm was prepared.
[0094] Example 1 The protective film (1) obtained above was immersed in a 1.5 mol / L NaOH aqueous solution (saponification solution) kept at a temperature of 55° C. for 2 minutes, and then washed with water. The washed protective film (1) was immersed in a 0.05 mol / L sulfuric acid aqueous solution at a temperature of 25° C. for 30 seconds, and then passed under running water for another 30 seconds to neutralize the protective film (1). The protective film (1) was repeatedly drained three times using an air knife, and then allowed to stay in a drying zone at a temperature of 70° C. for 15 seconds to dry. As a result, a saponified protective film (1) was obtained in which the HC layer and the base film were subjected to a saponification treatment (surface activation treatment).
[0095] A laminate (1) was obtained by laminating a saponified protective film (1) (hereinafter sometimes referred to as "first protective film (1)"), a polarizing film, and a retardation laminate via the PVA-based adhesive prepared above. In the laminate (1), the absorption axis of the polarizing film and the slow axis of the retardation film were parallel. In the laminate (1), the other retardation layer side of the retardation laminate was the polarizing film side, and the base film side of the first protective film (1) was the polarizing film side. The adhesive strength between the retardation laminate and the polarizing film, and the adhesive strength between the polarizing film and the first protective film (1) were sufficient for practical use.
[0096] Next, a saponified protective film (1) (hereinafter, sometimes referred to as "second protective film (1)"), which was saponified in the same manner as above, was laminated on the first protective film (1) side of the laminate (1) obtained above, via the adhesive layer A. The second protective film (1) had the base film side attached to the adhesive layer (A). In addition, the retardation laminate side of the laminate (1) was subjected to corona treatment, and the surface of the adhesive layer B was subjected to corona treatment, and the corona-treated surface of the laminate (1) and the corona-treated surface of the adhesive layer (B) were laminated together. In this way, a polarizing plate (1) was obtained. In the polarizing plate (1), the first protective film (1) and the second protective film (1) were both arranged on the same surface side of the polarizing film, the first protective film (1) was arranged relatively close to the polarizing film, and the second protective film (1) was arranged relatively far from the polarizing film.
[0097] Example 2 A polarizing plate (2) was obtained in the same manner as the polarizing plate (1) prepared in Example 1, except that a saponified protective film (2) was used that had been subjected to a saponification treatment similar to that performed on the protective film (1) instead of the first protective film (1) and the second protective film (1).
[0098] Example 3 A polarizing plate (3) was obtained in the same manner as the polarizing plate (1) prepared in Example 1, except that a saponified protective film (3) was used that had been subjected to a saponification treatment similar to that performed on the protective film (1) instead of the first protective film (1) and the second protective film (1).
[0099] Comparative Example 1 A comparative polarizing plate (C1) was obtained using the same procedure as that for preparing the polarizing plate (1) in Example 1, except that instead of the second protective film (1), a saponified substrate film (cellulose acylate film TD40, manufactured by Fujifilm Corporation, width 1,340 mm, film thickness 40 μm) was used that had been subjected to the same saponification treatment as that performed on the protective film (1).
[0100] Comparative Example 2 A laminate (1) was prepared in the same manner as in Example 1, and used as a comparative polarizing plate (C2).
[0101] Comparative Example 3 A comparative polarizing plate (C3) was obtained using a procedure similar to that for preparing the polarizing plate (1) in Example 1, except that instead of the first protective film (1), a saponified substrate film (cellulose acylate film TD40, manufactured by Fujifilm Corporation, width 1,340 mm, film thickness 40 μm) was used that had been subjected to the same saponification treatment as that performed on the protective film (1).
[0102] [Evaluation of crack occurrence] For each of the polarizing plates obtained in the examples and the comparative polarizing plates obtained in the comparative examples, evaluation samples were prepared according to the following procedure, and the occurrence of cracks was evaluated. The polarizing plate or the comparative polarizing plate was cut to a size of 200 mm x 200 mm, and attached to an alkali-free glass sheet having a thickness of 0.7 mm and a size of 300 mm x 300 mm via the adhesive layer B to prepare an evaluation sample.
[0103] The prepared evaluation samples were kept in a heating environment at a temperature of 105°C for 500 hours, and then cooled to a temperature of 23°C (room temperature). After that, they were kept in a room temperature and room humidity environment at a temperature of 23°C and a relative humidity of 55% for 30 days, and the retardation film of the polarizing plate or the comparative polarizing plate was observed to check for the occurrence of cracks. Furthermore, for the evaluation samples in which no cracks were observed at this point, the retardation film was observed after another 7 days (37 days after the start of keeping in the room temperature and room humidity environment) to check for the occurrence of cracks. The results are shown in Table 1.
[0104] [Table 1] [Explanation of symbols]
[0105] 1 polarizing plate, 11 polarizing film, 11a first surface, 11b second surface, 12, 13 protective film, 21 retardation film, 31 to 33 bonding layers, 35 adhesive layer.
Claims
1. a polarizing film in which a dichroic dye is adsorbed and oriented on a polyvinyl alcohol-based resin film; a protective film having a hard coat layer provided on a substrate film; A retardation film having a tensile modulus of elasticity of 3000 MPa or less at a temperature of 23° C.; Two or more of the protective films are laminated on the first surface side of the polarizing film, the retardation film is laminated on a second surface side of the polarizing film opposite to the first surface side, At least one of the two or more protective films laminated on the first surface side has a moisture permeability of 200 g / m at a temperature of 40° C. and a relative humidity of 90%. 2 ・day or more.
2. Of the two or more protective films laminated on the first surface side, the protective film laminated closest to the polarizing film has a moisture permeability of 200 g / m at a temperature of 40° C. and a relative humidity of 90%. 2 The polarizing plate according to claim 1 , wherein the polarizing plate has a polarizing effect of at least 100 nm.
3. 3 . The polarizing plate according to claim 1 , wherein the base film of at least one of the two or more protective films laminated on the first surface side is a cellulose-based resin film.
4. The polarizing plate according to any one of claims 1 to 3, wherein the retardation film is a cyclic olefin resin film.
5. 5. The polarizing plate according to claim 1, wherein the retardation film has an in-plane retardation value of 80 nm or more at a wavelength of 550 nm.
6. The polarizing plate according to any one of claims 1 to 5, further comprising a pressure-sensitive adhesive layer on the side of the retardation film opposite to the polarizing film side.
7. A display device comprising the polarizing plate according to claim 6 and a display element, The display device, wherein the polarizing plate is laminated on a display element via the pressure-sensitive adhesive layer.
Citation Information
Patent Citations
Liquid crystal panel, polarizing plate and liquid crystal display
JP2005345958A
Liquid crystal display device
JP2015022200A
Set of polarizing plates and liquid crystal panel
JP2017156398A
Composite polarizing plate and liquid crystal panel using same
WO2017047408A1
Tuning fork type bending resonator
JP1978083594A